LEGAL PROTECTION OF THE PARTIES IN THE CRYPTO ASSETS INVESTMENT AGREEMENT ON THE INDODAX WEBSITE VIEWING FROM CIVIL LAW ASPECTS - Nanda Tribramantya Purnama; Adhitya Widya Kartika (Universitas Islam Balitar, 2022)
Crypto can be interpreted as a data series that results from the formation of an electronic system, namely Cryptography that uses a peer-to-peer method in its work system, a system used as a transaction in cyberspace (cyber) will generate data or can also be referred to as an electronic document. . And by definition a crypto asset is a form of asset because crypto itself is also interpreted as an item that can be owned by a certain person or group and has economic value, which can be used and owned by legal entities or individuals. Therefore, Crypto is included in digital assets. It is the basis of Crypto users to make it not only as a means of payment but also as an asset for investment. Based on Article 1 Number 2 of the Commodity Futures Trading Act, crypto can be categorized as a commodity. Crypto is characterized by high volatility due to high price fluctuations. Crypto is legally declared as a commodity that can be traded in futures trading, namely as a crypto asset that can be used as the subject of a contract and then demands further regulation to be regulated by CoFTRA as a legal entity that carries out crypto transactions. The legal relationship that occurs between parties in the use of crypto can be known as a legal relationship between business actors and consumers or known as Business to Customer (B2C). PT. Indodax in this case can be called a business actor who offers digital asset exchange services and sells various types of digital assets to consumers (in this case users who are official members of PT. Indodax). Legal relationships are formed from the existence of electronic contracts. This can be a form of legal protection for consumers and businesses themselves.